Analisis Manajamen Risiko Kerugian Studi Kasus PT Asuransi Jiwa Manulife Indonesia pada Masa Pandemi - Nabila Putri Salsabila; Dian Hakip Nurdiansyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
PT. Asuransi Jiwa Manulife is one of the service companies engaged in isurance, where PT Asuransi Jiwa Mnulife has spread its wings in indonesia by cooperatinh with several companies, es pecially bankinh in Indonesia. So that its employees consist of competent people so that they can work in accordance with the vision of the company’s missions as well as having a role as the spearhead of insurance marketing. The leader is a positive and confident person who has a vision, mission and high ethical values, with the ability to convey ideas and be able in order to encourage and connrct well with others. Without a leader in the organization, an organization cannot be well organized and will not be effective in its implementation. Therefore, in need of good risk management, so that in its implementation can run well and able to identify, measure, and control various risks that will be faced.